2011
DOI: 10.1002/chem.201002069
|View full text |Cite
|
Sign up to set email alerts
|

Pentanary Cross‐Diffusion in Water‐in‐Oil Microemulsions Loaded with Two Components of the Belousov–Zhabotinsky Reaction

Abstract: We measure cross-diffusion coefficients in a five-component system, an aerosol OT (AOT) water-in-oil microemulsion loaded with two constituents of the Belousov-Zhabotinsky (BZ) reaction (H(2) O/AOT/BZ1/BZ2/octane). The species BZ1 is either NaBr, an inhibitor of the BZ reaction, or ferroin, a catalyst for the reaction. As species BZ2, we choose Br(2) , an intermediate in the reaction. The cross-diffusion coefficients between BZ1 and BZ2 are found to be negative, which can be understood in terms of complexation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 19 publications
(39 reference statements)
1
33
0
2
Order By: Relevance
“…Good qualitative agreement between the instability scenarios predicted by the theoretical model and the experimentally observed convective pattern is obtained. As the microemulsion system under study here is known to exhibit a large variety of patterns where crossdiffusion may couple to reaction processes, 7 our results provide characterisation of a good candidate for future studies of crossdiffusion-driven RDC instabilities. In the following sections, we introduce the cross-diffusive properties of AOT microemulsions and describe the experimental methods.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations
“…Good qualitative agreement between the instability scenarios predicted by the theoretical model and the experimentally observed convective pattern is obtained. As the microemulsion system under study here is known to exhibit a large variety of patterns where crossdiffusion may couple to reaction processes, 7 our results provide characterisation of a good candidate for future studies of crossdiffusion-driven RDC instabilities. In the following sections, we introduce the cross-diffusive properties of AOT microemulsions and describe the experimental methods.…”
Section: Introductionmentioning
confidence: 80%
“…In the following sections, we will refer to the concentration . 7 In particular, Table 1 reports the diffusion matrix D of a quaternary system where NaBrO 3 is the third component. Verification experiments were also run by using the colored salts KMnO 4 or K 2 Cr 2 O 7 in the place of NaBrO 3 .…”
Section: Experimental Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, cross-diffusion can modify any type of pattern, stationary, periodic or chaotic, and can even induce diffusive instability, Turing or wave [2,3]. Recent experiments [4][5][6] on the Belousov-Zhabotinsky reaction in a reverse microemulsion (BZ-AOT system [7]) have revealed that significant cross-diffusion takes place in this system, and model calculations [5] suggest that cross-diffusion effects should be large enough to affect BZ-AOT patterns.…”
Section: Introductionmentioning
confidence: 99%